INTRODUCTION (Fiep Bulletin - online, 2012)
It's a great honor & pleasure to be able to write the introduction of the 'South America FIEP History Magazine'. As any history has a beginning, this one begins on the 'II Stockholm Universal Sport Exhibition (Linguiade), Sweden', in 1949, where professionals of several South American countries took part on, and were introduced to this organization.